2021
DOI: 10.1007/s11033-021-06960-3
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to low dose ionizing radiation affects miR-21 and miR-625 expression levels

Abstract: Background Recently exposure to ionizing radiation driven by artificial radiation sources such as Medical X-rays and Nuclear medicine has increased hastily. Ionizing radiation-induced the DNA damage and activate the DNA damage response signaling pathways. The aim of this study was to evaluate the role of miR-21 and miR-625 in response to low-dose ionizing radiation. Materials and methodsIn this study, the blood sample of 38 volunteer patients who underwent Cardiac scans before and after 99m Tc-MIBI injection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The present study showed that the predicted target gene of miR-21 is SP1, which also makes sense in theory. To evaluate the role of miR-21 in response to low-dose ionizing radiation, a study was carried out on 38 volunteer patients, and bioinformatics analysis indicated that miR-21 can contribute to the response to acute low-dose ionizing radiation by targeting the SP1 (Mahmoudi et al, 2022 ). Yang et al found that miR-21 regulates CSE protein expression in vascular smooth muscles by regulating SP1 genes (Yang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the predicted target gene of miR-21 is SP1, which also makes sense in theory. To evaluate the role of miR-21 in response to low-dose ionizing radiation, a study was carried out on 38 volunteer patients, and bioinformatics analysis indicated that miR-21 can contribute to the response to acute low-dose ionizing radiation by targeting the SP1 (Mahmoudi et al, 2022 ). Yang et al found that miR-21 regulates CSE protein expression in vascular smooth muscles by regulating SP1 genes (Yang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since miRNA expression is a dynamic process, effective application of the proposed approach for cancer therapy may counterintuitively need to rely on combinations with other therapeutic approaches that upregulate the target oncogenic miRNA. For example, there is evidence that miR-21 is upregulated in response to ionizing radiation (Mahmoudi, et al, 2022). It is conceivable that neoadjuvant application of non-ablative ionizing radiation may synergize with the ss-ppp-miRNA-21 RIG-I agonist to produce improved anti-tumor responses.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) have also been suggested as potential candidates for early AD diagnosis (16). They are a group of non-coding RNAs, containing approximately 22 nucleotides, that regulate target genes (17)(18)(19). The evaluation of expression levels of circulating miRNAs in patients may aid in early AD diagnosis.…”
mentioning
confidence: 99%